Image Partitioning Methods in Spatial and Frequency Domain - M. Mahmood, Ahmed; Jasni, Mohamad Zain; M. Masroor, Ahmed (2012)

(untitled)
For partitioning the image, in spatial domain, contiguous neighbourhood pixels withsimilar properties are grouped together to make a region. These regions form processing blocks for the images during local enhancement. Additionally, many researchers, on the same pattern, divided the image histogram into many blocks. To split a candidate image or its histogram into regions, various methods are evolved by researchers. The paper reviews these existing partitioning methods and briefly illustrates the related contrast enhancement techniques. From this point onwards section one introduces the subject, section two, reviews existing partitioning techniques and section three presents conclusion by summarizing the paper.